2007
DOI: 10.1086/521833
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pneumococcal Conjugate Vaccine on Nasopharyngeal Colonization among Immunized and Unimmunized Children in a Community‐Randomized Trial

Abstract: (See the article by Lipsitch et al., on pages 1221-7.)Background. Pneumococcal conjugate vaccines (PCVs) prevent vaccine serotype (VT) invasive disease; nonvaccine serotype (NVT) disease increases modestly. The impact of PCV on nasopharyngeal (NP) colonization is essential to understanding disease effects.Methods. We conducted a community-randomized controlled trial with catch-up vaccination through age 2 years investigating the effect of 7-valent PCV (PnCRM7) on NP colonization among American Indian infants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(189 citation statements)
references
References 32 publications
10
171
1
7
Order By: Relevance
“…The decline in antibacterial use was faster for both older and younger children than for adults, although use in younger adults declined faster than for older adults. Possible reasons for these differences include: the influence of the pneumococcal conjugate vaccine on the perceived risk of child bacterial illness [43][44][45] and on parents' health through herd effects; 45,46 a potentially initially wider pool of unneeded antibacterial use in younger individuals; and a possible differential effect of demonstrated in this study, from 71% in 1990 to 59% in 2004, is similar to these US reports. Similarly, Steinman et al reported declining antibacterial use for child ARIs, from 41% in 1991 to 21% in 1999.…”
Section: Summary Of Main Findingssupporting
confidence: 70%
“…The decline in antibacterial use was faster for both older and younger children than for adults, although use in younger adults declined faster than for older adults. Possible reasons for these differences include: the influence of the pneumococcal conjugate vaccine on the perceived risk of child bacterial illness [43][44][45] and on parents' health through herd effects; 45,46 a potentially initially wider pool of unneeded antibacterial use in younger individuals; and a possible differential effect of demonstrated in this study, from 71% in 1990 to 59% in 2004, is similar to these US reports. Similarly, Steinman et al reported declining antibacterial use for child ARIs, from 41% in 1991 to 21% in 1999.…”
Section: Summary Of Main Findingssupporting
confidence: 70%
“…Among parents of vaccinated children, carriage of PCV7 serotypes had almost disappeared. This impressive reduction of PCV7-serotype carriage in infants is larger than that observed in clinical trials, which showed 50%-60% reduction in PCV7 rates after conjugate vaccination, and should be attributed to herd effects (13,18,19). Herd effects would also account for the disappearance of PCV7 serotypes in parents.…”
Section: Discussionmentioning
confidence: 71%
“…An immunoblot method designed to detect multiple serotypes in carriage studies was used in a study in Navajo and White Mountain Apache reservations. Multiple serotypes were detected in 8.1% of positive samples (6,34). In a study of pneumococcal carriage in the Gambia, serotyping was performed by latex agglutination, and multiple serotypes were identified in 11.5% of positive samples (30).…”
Section: Discussionmentioning
confidence: 99%